Penempatan Kapasitor Paralel pada Penyulang Pajajaran GI Jakabaring - Wiwin A Oktaviani; Supri Suhendra; Taufik Barlian (Jurnal Rekayasa Elektro Sriwijaya, 2022)
In order to compensate for reactive power on electrical power distribution lines, parallel capacitors have been utilized extensively. Capacitor placement does not constantly improve the total voltage and power factor. Therefore, it is crucial to establish the ideal capacitance (size) and position of the capacitors to reduce power losses in the distribution line. Palembang City's New Jakabaring Substation is a substation situated in a region with a rapid load increase. Pajajaran Feeder, one of the several feeders at this substation, carries the weight of numerous significant loads as well as expanding residential areas. Reactive power computation and optimal capacitor placement (OCP) were the two simulation techniques used in the study, which were carried out using ETAP 19.0. The study's findings demonstrate that using reactive power calculations, the original Padjajaran feeder voltage drop is improved from 93.26% to 98.98% while utilizing OCP, the voltage drop is improved from 93.26% to 100.1%. However, OCP provides a more consistent capacitance value of the capacitors in the range of 930 kVAR compared to reactive power calculations, whose results are more inconsistent. Calculations using OCP gives more capacitors, namely as many as 20 more than those produced by calculating the reactive power of 14 capacitors. The location of parallel capacitors in the Padjajaran feeder can function optimally and support a load of up to 80% of the transformer capacity rating.